Avaliação de novos marcadores prognósticos e preditivos em neoplasia mamária de cadelas: avaliação sérica e molecular do VEGF e do HIF-1α - Moschetta, Marina Gobbe (2013)
Introduction: Mammary tumors are the most common type of tumor in dogs, with approximately half of these tumors are malignant. Hypoxia, characterized by oxygen levels below normal, is a known adverse factor to cancer treatment. The transcription factor HIF-1α is the central regulator of pathophysiological response of mammalian cells to low oxygen levels, able to activate transcription of the vascular endothelial growth factor (VEGF), which in turn promotes angiogenesis through its ability to stimulate growth, migration and invasion of endothelial cells, contributing to tumor growth. Objectives: To evaluate the serum concentration and the gene expression of VEGF and HIF-1α linking them with clinicopathological parameters and survival of dogs with mammary tumors in order to infer the possible prognostic value of these factors. Material and Methods: We collected tumor fragments of 30 bitches with mammary tumors to verify protein expression of VEGF and HIF-1α by immunohistochemistry and gene expression by RT-PCR. To determine the serum concentration of VEGF and HIF-1α by ELISA (Enzyme-linked immunosorbent), serum was collected from 50 bitches control (healthy) and 30 bitches with mammary neoplasia (study group). The results were statistically related to clinicopathological features. Results: The comparison between immunohistochemical staining of the two proteins analyzed showed increased intensity of immunostaining of VEGF (p=0.03). By ELISA, we observed relationship between high serum levels of VEGF and abundant vascularization (p=0.02), metastasis (p=0.003), death rate (p=0.007) and low survival (p<0.0001). In addition, increased serum levels of VEGF in the study group compared to the control group (p=0.03). In contrast, the percentage of serum HIF-1α bitches with mammary neoplasia was 20% lower than the control group of female dogs (p=0.0006). However, bitches with a history of recurrent tumor showed a 15% increase in the percentage of serum HIF-1α (p=0.03). Regarding gene expression, there was a relationship between increased gene expression of VEGFA and tumor abundant vascularization (p=0.02), bitches with a history of recurrence (p=0.01) and death (p=0.02). Moreover, we observed a statistically significant increase in gene expression of HIF-1A with moderate vascularization (p=0.01) and bitches that remained alive during the follow-up period (p=0.003). Conclusions: Our results demonstrate a correlation between VEGF and features of poor prognosis, suggesting that this factor plays an important role in tumor progression and can be used as a potential prognostic marker in clinical practice and is useful in predicting tumor progression in dogs with mammary neoplasia.